Crohn’s Disease Associated to Chordoma - De Jesús-Monge, Wilfredo E.; Torres, Esther A.; Báez, Virgen M.; De Jesús, Orlando; Rivera, Lumarie; González-Keelan, Carmen (Puerto Rico Health Sciences Journal, 2010)
see manuscript